Investigating the strategic antecedents of agility in humanitarian logistics. Issue 4 (16th December 2016) - L'Hermitte, Cécile; Brooks, Benjamin; Bowles, Marcus; Tatham, Peter H.
Abstract : This study investigates the strategic antecedents of operational agility in humanitarian logistics. It began by identifying the particular actions to be taken at the strategic level of a humanitarian organisation to support field‐level agility. Next, quantitative data (n=59) were collected on four strategic‐level capabilities (being purposeful, action‐focused, collaborative, and learning‐oriented) and on operational agility (field responsiveness and flexibility). Using a quantitative analysis, the study tested the relationship between organisational capacity building and operational agility and found that the four strategic‐level capabilities are fundamental building blocks of agility. Collectively they account for 52 per cent of the ability of humanitarian logisticians to deal with ongoing changes and disruptions in the field. This study emphasises the need for researchers and practitioners to embrace a broader perspective of agility in humanitarian logistics. In addition, it highlights the inherently strategic nature of agility, the development of which involves focusing simultaneously on multiple drivers.